Acute exercise induces distinct quantitative and phenotypical T cell profiles in men with prostate cancer - Erik D. Hanson; Erik D. Hanson; Erik D. Hanson; Erik D. Hanson; Samy Sakkal; Lauren C. Bates-Fraser; Lauren C. Bates-Fraser; Lauren C. Bates-Fraser; Shadney Que; Eunhan Cho; Guillaume Spielmann; Elif Kadife; et al. (Frontiers Media S.A., 2023)
BackgroundReduced testosterone levels can influence immune system function, particularly T cells. Exercise during cancer reduces treatment-related side effects and provide a stimulus to mobilize and redistribute immune cells. However, it is unclear how conventional and unconventional T cells (UTC) respond to acute exercise in prostate cancer survivors compared to healthy controls.MethodsAge-matched prostate cancer survivors on androgen deprivation therapy (ADT) and those without ADT (PCa) along with non-cancer controls (CON) completed ∼45 min of intermittent cycling with 3 min at 60% of peak power interspersed by 1.5 min of rest. Fresh, unstimulated immune cell populations and intracellular perforin were assessed before (baseline), immediately following (0 h), 2 h, and 24 h post-exercise.ResultsAt 0 h, conventional T cell counts increased by 45%-64% with no differences between groups. T cell frequency decreased by −3.5% for CD3+ and −4.5% for CD4+ cells relative to base at 0 h with CD8+ cells experiencing a delayed decrease of −4.5% at 2 h with no group differences. Compared to CON, the frequency of CD8+CD57+ cells was −18.1% lower in ADT. Despite a potential decrease in maturity, ADT increased CD8+perforin+ GMFI. CD3+Vα7.2+CD161+ counts, but not frequencies, increased by 69% post-exercise while CD3+CD56+ cell counts increased by 127% and were preferentially mobilized (+1.7%) immediately following the acute cycling bout. There were no UTC group differences. Cell counts and frequencies returned to baseline by 24 h.ConclusionFollowing acute exercise, prostate cancer survivors demonstrate normal T cell and UTC responses that were comparable to CON. Independent of exercise, ADT is associated with lower CD8+ cell maturity (CD57) and perforin frequency that suggests a less mature phenotype. However, higher perforin GMFI may attenuate these changes, with the functional implications of this yet to be determined.